IMPLIKASI INSTRUKSI PRESIDEN NOMOR 1 TAHUN 2025 TENTANG EFISIENSI ANGGARAN TERHADAP PELAKSANAAN PENDIDIKAN TINJAUAN AL-MASLAHAH - Rizky Khoir, Muhammad; Ramadhan, Muhammad (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Budget efficiency is a government policy aimed at optimizing state financial management amidst fiscal constraints. The issuance of Presidential Instruction Number 1 of 2020 concerning Budget Efficiency has raised concerns about the education sector due to its potential impact on the fulfillment of basic community rights. This study aims to analyze education budget efficiency policies from a maslahah (benefit) perspective. This research uses a normative juridical method with a conceptual approach and statutory regulations. Data were obtained through literature review and analyzed descriptively and analytically. The results indicate that budget efficiency policies can be considered maslahah ‘ammah (benefit) if their implementation does not reduce the substance of the education budget and still ensures the sustainability of strategic programs such as the School Operational Assistance (BOS), the Public Service Program (PIP), and the Public Service Program (KIP Kuliah). However, budget efficiency has the potential to cause maslahah (benefit) if implemented without considering regional fiscal conditions and capacity, particularly regarding the reduction of Regional Transfers (TKD). Therefore, budget efficiency policies can be justified selectively, proportionally, and oriented towards the public good.